Fear-related behaviors in situations of mass threat. Issue 4 (1st October 2016) - Espinola, Maria; Shultz, James M.; Espinel, Zelde; Althouse, Benjamin M.; Cooper, Janice L.; Baingana, Florence; Marcelin, Louis Herns; Cela, Toni; Towers, Sherry; Mazurik, Laurie; Greene, M. Claire; Beck, Alyssa; et al.
ABSTRACT: This Disaster Health Briefing focuses on the work of an expanding team of researchers that is exploring the dynamics of fear-related behaviors in situations of mass threat. Fear-related behaviors are individual or collective behaviors and actions initiated in response to fear reactions that are triggered by a perceived threat or actual exposure to a potentially traumatizing event. Importantly, fear-related behaviors modulate the future risk of harm . Disaster case scenarios are presented to illustrate how fear-related behaviors operate when a potentially traumatic event threatens or endangers the physical and/or psychological health, wellbeing, and integrity of a population. Fear-related behaviors may exacerbate harm, leading to severe and sometimes deadly consequences as exemplified by the Ebola pandemic in West Africa. Alternatively, fear-related behaviors may be channeled in a constructive and life-saving manner to motivate protective behaviors that mitigate or prevent harm, depending upon the nature of the threat scenario that is confronting the population. The interaction between fear-related behaviors and a mass threat is related to the type, magnitude, and consequences of the population encounter with the threat or hazard. The expression of FRBs, ranging from risk exacerbation to risk reduction, is also influenced by such properties of the threat as predictability, familiarity, controllability, preventability, and intentionality.